1986
DOI: 10.1071/ch9860419
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Pyrrolic Compounds. LIX. The Oxidative Cyclization of Bilenes-b Substituted by Ethyl or Propyl Groups at a Terminal Site

Abstract: Oxidative cyclization of bilenes -b substituted with an ethyl or propyl group at one terminal site and a formyl equivalent at the other yields substantial quantities of the meso-ethyl- or meso-propyl-porphyrin. The origin of these meso-substituents has been substantiated by a study of a deuterated analogue. The copper chelate of the meso-ethylporphyrin (2d) seems unexpectedly stable in acid allowing the formation of by- products involving the interaction of the meso-substituent and the adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These molecules have been most popular for their use in the synthesis of porphyrins, chlorins, , and tetrahydrocorrins. , The 1,19-dimethyl-derivatives, sometimes formed in situ, have also been used to synthesize metalloporphyrins by cyclization in the presence of metal ions. From the earliest of these metal cyclization reactions it was discovered that bilene- b analogues form homoleptic metal complexes . This work was extended to investigate the metal-complex geometries of dipyrrins through a study upon bilene- b metal complexes such as compound 72 : it was shown that they displayed complexation behavior similar to that of 1,9-sterically hindered dipyrrins (Figure ). ,
72 Structure of a zinc(II) bilene- b complex.
…”
Section: 5 Bilene-b Complexesmentioning
confidence: 99%
“…These molecules have been most popular for their use in the synthesis of porphyrins, chlorins, , and tetrahydrocorrins. , The 1,19-dimethyl-derivatives, sometimes formed in situ, have also been used to synthesize metalloporphyrins by cyclization in the presence of metal ions. From the earliest of these metal cyclization reactions it was discovered that bilene- b analogues form homoleptic metal complexes . This work was extended to investigate the metal-complex geometries of dipyrrins through a study upon bilene- b metal complexes such as compound 72 : it was shown that they displayed complexation behavior similar to that of 1,9-sterically hindered dipyrrins (Figure ). ,
72 Structure of a zinc(II) bilene- b complex.
…”
Section: 5 Bilene-b Complexesmentioning
confidence: 99%
“…The chemistry reported paralleled the electrochemical synthesis of porphyrins from a , c -biladiene salts , and enabled a deeper understanding of the mechanistic pathways , from a , c -biladienes to copper(II) porphyrins , and to metal-free porphyrins using the chromium procedure recently described by Boschi and co-workers . Other studies have also probed the nature of the metal salt oxidant used, as well as methodology for generalization of the synthetic route through the preparation of unsymmetrically substituted a , c -biladienes and porphyrins therefrom. , Parallel synthetic and mechanistic studies of the synthesis of porphyrins from b -bilenes have also been reported by Clezy and co-workers, and their results are broadly in agreement with our own conclusions for a , c -biladienes.
1 Formation of Novel Macrocycles from Copper(II)-Catalyzed Oxidative Cyclization of a , c -Biladiene Dihydrobromide ( 1 ) 1
…”
Section: Introductionmentioning
confidence: 91%
“…However, for activated electrophiles reagents, such as allyl bromide and benzyl bromide, the yields were found to be slightly lower than that for nonactivated electrophiles. This is not that surprising since it has previously been documented [21] that activated electrophiles prefer Oalkylation of enolates (derived from 1,3-dicarbonyl derivatives) to give enol ethers rather than traditional C-alkylation [22]. We next turned our attention to the synthesis of unsymmetrical di-substituted…”
mentioning
confidence: 90%